2009
DOI: 10.1111/j.1464-410x.2009.08471.x
|View full text |Cite
|
Sign up to set email alerts
|

Acute urinary retention and subsequent catheterization cause lipid peroxidation and oxidative DNA damage in the bladder: preventive effect of edaravone, a free‐radical scavenger

Abstract: 30 min and then the bladder was allowed to drain with a catheter in place for 60 min as the studies continued. After killing the rats the function of the bladder was assessed, with carbachol and 100 m M KCl, and the levels of malondialdehyde (MDA, a marker of lipid peroxidation), 8-hydroxydeoxyguanosine (8-OHdG; a marker of oxidative DNA damage), heat-shock protein 70 (HSP 70) and its mRNA were measured. RESULTSAUR increased the intravesical pressure and decreased blood flow, and subsequent catheterization dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(52 citation statements)
references
References 27 publications
2
50
0
Order By: Relevance
“…Clinically, bladder dysfunction is sustained after acute urinary retention (AUR) (84). In turn, AUR and subsequent catheterization may enhance lipid peroxidation and oxidative DNA damage in the rat bladder.…”
Section: Bladder Injurymentioning
confidence: 99%
“…Clinically, bladder dysfunction is sustained after acute urinary retention (AUR) (84). In turn, AUR and subsequent catheterization may enhance lipid peroxidation and oxidative DNA damage in the rat bladder.…”
Section: Bladder Injurymentioning
confidence: 99%
“…Previous research has shown that edaravone plays an important role as a direct and indirect free radical scavenger by neutralizing toxic ROS and reactive nitrogen species (RNS) (Roh et al 2011). Importantly, edaravone has been found to protect DNA from oxidative stress (Shimizu et al 2009). These mechanisms require the presence of edaravone at the time of radiation in cells and tissues.…”
mentioning
confidence: 99%
“…Edaravone reduced the levels of HSP 70 (a marker of stress) and its mRNA in an I/R-induced rat testicular torsion model (31). Edaravone also markedly reduced the expression levels of HSP 70 and its mRNA and prevented bladder dysfunction caused by AUR and subsequent catheterization in rats (60).…”
Section: Effects Of Edaravone On Heat Shock Proteins (Hsps)mentioning
confidence: 94%
“…Acute urinary retention (AUR) and subsequent catheterization caused lipid peroxidation and oxidative DNA damage in the rat bladder (60). Edaravone induced a decrease in blood flow in the bladder during urinary retention and subsequent catheterization (60).…”
Section: Pharmacological Effects Of Edaravone In Non-neurologic Diseasesmentioning
confidence: 99%
See 1 more Smart Citation